Design and development of DrawBot using image processing - Krithika Vaidyanathan; Nandhini Murugan; Subramani Chinnamuthu; Sivashanmugam Shivasubramanian; Surya Raghavendran; Vimala Chinnaiyan (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Extracting text from an image and reproducing them can often be a laborious task. We took it upon ourselves to solve the problem. Our work is aimed at designing a robot which can perceive an image shown to it and reproduce it on any given area as directed. It does so by first taking an input image and performing image processing operations on the image to improve its readability. Then the text in the image is recognized by the program. Points for each letter are taken, then inverse kinematics is done for each point with MATLAB/Simulink and the angles in which the servo motors should be moved are found out and stored in the Arduino. Using these angles, the control algorithm is generated in the Arduino and the letters are drawn.